Understanding Healthcare Personnel’s Perceptions About Reducing Low-Value Care: A Scoping Review - Li J; Yang D (Risk Management and Healthcare Policy)
Jiamin Li,1 Dan Yang2 1School of Nursing, Hangzhou Normal University, Hangzhou, Zhejiang, 311121, People’s Republic of China; 2School of Nursing, Beijing University of Chinese Medicine, Beijing, 100029, People’s Republic of ChinaCorrespondence: Jiamin Li, School of Nursing, Hangzhou Normal University, No. 2318, Yuhangtang Road, Yuhang District, Hangzhou, Zhejiang, 311121, People’s Republic of China, Email lijiamin9@163.comObjective: To systematically and comprehensively search the studies describing healthcare personnel’s perceptions about reducing low-value care.Design: Scoping review.Methods: Evidence sources included PubMed, ProQuest and CINAHL databases from inception to 13th September 2023, along with grey literature, expert suggestions and reference lists from the included articles. Studies were included if they contained information about healthcare personnel’s perceptions and involvement in reducing low-value care. The extracted data included general study characteristics, the type of low-value care of interest, clinical settings, and main findings related to healthcare personnel’s perceptions. Three frameworks were used to guide the data synthesis. First, the main findings from the included studies were mapped onto the Process of De-adoption Framework to capture the aspects of low-value care that healthcare personnel focused on, including the identification of low-value care, barriers and facilitators to reducing low-value care, and intervention strategies. The identified barriers and facilitators were then mapped onto the relevant domains of the Theoretical Domains Framework. Finally, the intervention strategies, as informed by healthcare personnel’s perceptions, were mapped to the Cochrane Effective Practice and Organization of Care taxonomy framework.Results: The 37 included studies were those published since 2011. Of these, 15 studies were conducted in the United States. Most included studies (n = 19) described low-value care not specific to a care measure. Twelve of the included studies described healthcare personnel’s perceptions regarding the identification of low-value care, 34 studies described healthcare personnel’s perceptions regarding influence factors to reducing low-value care and 18 studies described healthcare personnel’s perceptions regarding intervention strategies to reduce low-value care. “Knowledge” (n = 16) and ‘environmental context and resources’ (n = 16) were the most common influence factors of reducing low-value care. “Education” was the most commonly discussed intervention strategy for reducing low-value care (n = 14).Conclusion: Healthcare personnel’s perceptions focused on identifying low-value care, barriers and facilitators of reducing low-value care and intervention strategies to reduce low-value care. Education was potentially the main effect of the intervention strategies in addressing lack of knowledge, which is the main barrier to reducing low-value care. Future research should develop and implement intervention strategies to reduce low-value care based on healthcare personnel’s perceptions.Keywords: low-value care, reducing, de-implementation, evidence-based practice